PERANAN BERBAGAI MACAM MEDIA TUMBUH BAGI PERTUMBUHAN STEK DAUN JERUK J.C (Japanche citroen) DENGAN BEBERAPA KONSENTRASI BAP - Oksana Oksana; Elfi Rahmadani; Syamsul Syamsul (Jurnal Agroteknologi, 2012)
This study was conducted from July to October 2011 in the green house of Genetics and Breeding Laboratory Faculty of Agriculture and Animal Science of State Islamic University Sultan Syarif Kasim Riau. The research objective was to observe growth in cuttings up to the growth of buds on each of the growing medium with various concentrations of BAP. This research used randomized complek block design (RCBD) Factorial: the first factor two different growing media (sand and soil) while the second factor was four level BAP concentrations (0, 200, 300, 400 ppm) with three replication. Variables analyzed were the survival percentage, the percentage of shoots growth, while emerging shoots, shoot length, number of leaf and number of roots. Data were analyzed by analysis of variance. The results showed that different of growing media significantly influenced the survival percentage and number of root cuttings JC media lime leaves that soil media more than sand, but BAP concentration and interaction between the growing medium and BAP concentration did not affect significantly the survival percentage and number of roots.